2009
DOI: 10.1088/0004-637x/707/1/768
|View full text |Cite
|
Sign up to set email alerts
|

Substellar-Mass Companions to the K-Dwarf Bd+14 4559 and the K-Giants Hd 240210 and Bd+20 2457

Abstract: We present the discovery of substellar-mass companions to three stars by the ongoing Penn State -Toruń Planet Search (PTPS) conducted with the 9.2-m Hobby-Eberly Telescope. The K2-dwarf, BD +14 4559, has a 1.5 M J companion with the orbital period of 269 days and shows a non-linear, long-term radial velocity trend, which indicates a possible presence of another planet-mass body in the system. The K3-giant, HD 240210, exhibits radial velocity variations that require modeling with multiple orbits, but the availa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 50 publications
3
90
0
1
Order By: Relevance
“…A quick look at literature data allows us to speculate on the possibility that the brown dwarf desert may not be very "dry" when it comes to close substellar companions to intermediatemass stars, in light of a handful of systems containing at least one companion with minimum mass in the brown dwarf regime (e.g., Omiya et al 2009, and references therein). In particular, the recently announced system of brown dwarfs around BD+20 2457 (Niedzielski et al 2009) has an architecture very similar to that of HD 168443, with a solar-type primary. It is reminiscent of an origin in a massive circumstellar disk, further suggesting a scenario in which more massive substellar companions are found around more massive stellar hosts (and their frequency also increases with increasing primary mass).…”
Section: The Role Of the Primary Mass And Metallicitymentioning
confidence: 97%
“…A quick look at literature data allows us to speculate on the possibility that the brown dwarf desert may not be very "dry" when it comes to close substellar companions to intermediatemass stars, in light of a handful of systems containing at least one companion with minimum mass in the brown dwarf regime (e.g., Omiya et al 2009, and references therein). In particular, the recently announced system of brown dwarfs around BD+20 2457 (Niedzielski et al 2009) has an architecture very similar to that of HD 168443, with a solar-type primary. It is reminiscent of an origin in a massive circumstellar disk, further suggesting a scenario in which more massive substellar companions are found around more massive stellar hosts (and their frequency also increases with increasing primary mass).…”
Section: The Role Of the Primary Mass And Metallicitymentioning
confidence: 97%
“…However, some recent programs have been monitoring also more massive stars, such as evolved subgiants and giants (e.g., Hatzes et al 2006;Döllinger et al 2009;Niedzielski et al 2009;Johnson et al 2011;Sato et al 2013) as well as A-F-type mainsequence stars (e.g., Galland et al 2005;Guenther et al 2009;Hartmann et al 2010;Borgniet et al 2014). One of our targets was the roAp star HD 42659.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…This offers an excellent opportunity to improve our understanding of the population of planets around stars that are significantly more massive than the Sun, without which it would be difficult to produce abroad, integrated picture of planet formation and evolution. Since 2001, about 30 such objects have been identified, including our five published HET detections (Niedzielski et al 2007;Niedzielski et al 2009a;Niedzielski et al 2009b). Our work has produced the tightest orbit of a planet orbiting a K-giant identified so far (0.6 AU), and the first convincing evidence for a multiplanet system around such as star (Niedzielski et al 2009a).…”
mentioning
confidence: 62%
“…Our work has produced the tightest orbit of a planet orbiting a K-giant identified so far (0.6 AU), and the first convincing evidence for a multiplanet system around such as star (Niedzielski et al 2009a). Our most recent discoveries (Niedzielski et al 2009b) have identified new multiplanet systems, including a very intriguing one of two brown dwarf-mass bodies orbiting a 2.8M , K2 giant. This particular detection challenges the standard interpretation of the so-called brown dwarf desert known to exist in the case of solar-mass stars.…”
mentioning
confidence: 64%